Lemongrass essential oil and its components cause effects on survival, locomotion, ingestion, and histological changes of the midgut in Anticarsia gemmatalis caterpillars. (2nd January 2022) - Plata-Rueda, Angelica; Fiaz, Muhammad; Brügger, Bruno Pandelo; Cañas, Veronica; Coelho, Rogerio Pereira; Zanuncio, José Cola; Martínez, Luis Carlos; Serrão, José Eduardo
Abstract: Anticarsia gemmatalis caterpillar is controlled with synthetic insecticides, which cause environmental pollution and insect resistance, and new compounds with low environmental impact, need to be investigated. Toxicity, survival, locomotion, feeding, and midgut histopathology of A. gemmatalis caterpillars exposed to lemongrass essential oil (LEO) and its components (citral and geranyl acetate) were investigated. The compounds are toxic to caterpillars with survival decreasing according to concentration. The compounds decrease insect respiration rate, cause repellency responses and midgut histopathological effects in the digestive and globet cells. These findings suggest that these compounds can be alternatives to chemical synthetic insecticides to control this insect.